2022
DOI: 10.1002/pon.5894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on cancer patients and psycho‐oncology providers: Perspectives, observations, and experiences of the American Psychosocial Oncology Society membership

Abstract: Objective To understand: (1) psycho‐oncology providers' perspectives on and observations of the psychological responses of their cancer patients during the pandemic, and (2) psycho‐oncology providers' own experiences delivering care. Methods In this concurrent mixed methods study, a survey was distributed to psychosocial providers who were members of the American Psychosocial Oncology Society (APOS). Survey respondents were invited to participate in a one‐on‐one audio‐recorded interview via phone or secure Zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Economic side effects of the pandemic on the individual patient level, such as unemployment and loss of health care insurance, were identified in one study on reasons behind reduced cancer screening rates in the USA [39]. Possibly, health care providers in industrialized countries should develop more trust in measures adopted to counteract effects of the pandemic [40, 41]. Since most prior studies on the topic are based on survey data from health care providers or patients, more “hard” data based on actual health care records (as provided in the present study) or national registers are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Economic side effects of the pandemic on the individual patient level, such as unemployment and loss of health care insurance, were identified in one study on reasons behind reduced cancer screening rates in the USA [39]. Possibly, health care providers in industrialized countries should develop more trust in measures adopted to counteract effects of the pandemic [40, 41]. Since most prior studies on the topic are based on survey data from health care providers or patients, more “hard” data based on actual health care records (as provided in the present study) or national registers are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of cancer survivors suggested that older age may mitigate the impact of Covid-19 related stressors, with older adults redeploying and repurposing coping previously used for cancer and other health concerns ( 202 ). A recent study found that successfully navigating a cancer diagnosis and treatment may have prepared cancer survivors for the existential distress of the pandemic and conferred additional resilience ( 203 ).…”
Section: Biobehavioral Factors That Confer Resiliencementioning
confidence: 99%
“…The global COVID-19 pandemic has been an existential provocateur—activating existential anxiety associated with mortality awareness in the general population (Tomaszek & Muchacka-Cymerman, 2020) and disrupting the goals and plans that create meaning and purpose in people’s lives (Ritchie et al, 2020). For cancer survivors, already at risk of existential distress (Vehling & Kissane, 2018), COVID-19 created additional burdens (McAndrew et al, 2022). With treatments interrupted and surgeries canceled, patients with immunosuppression faced even greater activity restrictions than the general public (Frey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%